Refractory Biliary Catheter Leak Corrected by a Hybrid Closed Loop Catheter-Pump System. (9th March 2021) - Murthy, Ravi; Rachakonda, Varun; Bassuner, Juri
Abstract : The development of inoperable biliary obstruction in patients with liver, biliary, and pancreatic neoplasia is commonplace particularly in the advanced stages of these diseases. Under these circumstances, restoring bile flow to the gut is paramount in reestablishing homeostasis. Hitherto, this has been achieved by utilizing passive, gravity-dependent bilioenteric conduits with the use of perforated plastic catheters or metallic stents inserted either in a percutaneous transhepatic fashion or via endoscopic techniques. A frequent untoward event of biliary decompression utilizing percutaneous transhepatic catheters (PTC) is the development of pain, cholangitis, hyperbilirubinemia, or pericatheter bile leak due to the suboptimal normalization of bile flow. In some instances, the etiology of PTC malfunction can be correctly ascribed to catheter malposition and/or catheter lumen obstruction; however, in the majority, it remains radiographically occult on transcatheter cholangiography—the "gold standard." Regardless of findings, the management remains fluoroscopic repositioning or exchanges for larger diameter catheters to attempt to seal the pericatheter potential space and prevent bile seepage. Unfortunately, these maneuvers are met with limited and unpredictable levels of success. We present the successful management of an instance of recalcitrant external pericatheter bile leak mitigated by employing a hybrid closed loop biliary catheter-pump system by employing an assortment of FDA approved off-the-shelf medical devices.